Prevalence and associations of non-retinopathy ocular conditions among older Australians with self-reported diabetes: The National Eye Health Survey - Foreman, Joshua (Int J Ophthalmol, 2020)
AIM: To determine the prevalence and associations of non-retinopathy ocular conditions among older Australian adults with diabetes. METHODS: Multistage random-cluster sampling was used to select 3098 non-indigenous Australians aged 50y or older (46.4% male) and 1738 indigenous Australians aged 40y or older (41.1% male) from all levels of geographic remoteness in Australia. Participants underwent a standardised questionnaire to ascertain diabetes history, and a clinical examination to identify eye disease. We determined the prevalence of uncorrected refractive error, visually significant cataract, cataract surgery, age-related macular degeneration, glaucoma, ocular hypertension, retinal vein occlusion and epiretinal membrane among those with and without self-reported diabetes. RESULTS: Participants with self-reported diabetes had a higher prevalence of cataract surgery than those without diabetes (28.8% vs 16.9%, OR 1.78, 95%CI: 1.35-2.34 among non-indigenous Australians, and 11.3% vs 5.2%, OR 1.62, 95%CI: 1.22-2.14 among indigenous Australians). Diabetic retinopathy (DR) increased the odds of cataract surgery among self-reported diabetic indigenous and non-indigenous Australians (OR 1.89, P=0.004 and OR 2.33, P<0.001 respectively). Having diabetes for ≥20y and having vision-threatening DR increased the odds of cataract surgery among indigenous Australians with diabetes (OR 3.73, P=0.001 and 7.58, P<0.001, respectively). CONCLUSION: Most non-retinopathy ocular conditions are not associated with self-reported diabetes. However, to account for Australia's worsening diabetes epidemic, interventions to reduce the impact of diabetes-related blindness should include increased cataract surgery services.